2019
DOI: 10.1017/s0007123419000383
|View full text |Cite
|
Sign up to set email alerts
|

How Political Contestation Over Judicial Nominations Polarizes Americans’ Attitudes Toward the Supreme Court

Abstract: Contemporary US Supreme Court nominations are unavoidably and inevitably political. Although observers worry that political contestation over nominations undermines support for qualified nominees and threatens the Court's legitimacy, there is little empirical evidence to support these claims. The authors argue that political contestation over judicial nominations provides cues that shape the public's impressions about nominees and the Court and polarizes public opinion across partisan lines. Data from a conjoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 41 publications
4
39
0
1
Order By: Relevance
“…Finally, our findings join the growing chorus of evidence that the legitimacy of the Supreme Court is not as stable as the conventional wisdom might suggest. While previous studies demonstrate the effects of ideological distance (Bartels and Johnson, 2013), confirmation hearings (Rogowski and Stone, 2019;Armaly, 2018b), and the decisions of the Court itself (Christenson and Glick, 2015;Zilis, 2018) on support for the institution, our findings join recent work highlighting the importance of confirmation hearings and the justices themselves on institutional support.…”
Section: Discussionsupporting
confidence: 80%
“…Finally, our findings join the growing chorus of evidence that the legitimacy of the Supreme Court is not as stable as the conventional wisdom might suggest. While previous studies demonstrate the effects of ideological distance (Bartels and Johnson, 2013), confirmation hearings (Rogowski and Stone, 2019;Armaly, 2018b), and the decisions of the Court itself (Christenson and Glick, 2015;Zilis, 2018) on support for the institution, our findings join recent work highlighting the importance of confirmation hearings and the justices themselves on institutional support.…”
Section: Discussionsupporting
confidence: 80%
“…Research has shown that much of the criticism directed at the US Supreme Court has often been realized within a political frame, involving claims that the justices make decisions on ideological grounds and that the Court has usurped powers that belong to other branches of government (e.g., Bybee, 2010). Moreover, framing the US Supreme Court as a political rather than a legal institution has been associated with a decline in the perceived legitimacy of the Court (e.g., Andersen‐Jones, 2014; Hitt & Searles, 2018; LaRowe & Hoekstra, 2014; Rogowski & Stone, 2019). 24…”
Section: Resultsmentioning
confidence: 99%
“…Thus, political framing is found in recurring references to the personal ideologies of candidates to the US Supreme Court (Sen, 2017), in reports about the activism of the Court in reviewing legislation, and in descriptions of behind the scenes bargaining among the justices and vis‐à‐vis other political actors (Hitt & Searles, 2018; Solberg & Waltenburg, 2014). This political framing has been associated with a decline in public support for the Court (e.g., Andersen‐Jones, 2014; Hitt & Searles, 2018; LaRowe & Hoekstra, 2014; Rogowski & Stone, 2019).…”
Section: Media Framing and Public Support For Supreme Courtsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Bartels and Johnston (2012), the American public perceives the judiciary in explicitly political terms and desires that Supreme Court justices are chosen on the basis of their political beliefs. Consistent with this perspective, Sen (2017) demonstrates that political views are the most important factor in how the public evaluates judicial nominees (see also Rogowski and Stone, Forthcoming). Given the salience of political considerations for attitudes toward judges and justices, descriptive characteristics may be especially important in the context of nominations because nominations exemplify low-information environments.…”
Section: Demographic Representation and The Judiciarymentioning
confidence: 90%